Germline rare variants in HER2-positive breast cancer predisposition: a systematic review and meta-analysis - de Baumont, Angelica Cerveira; Cadore, Nathan Araujo; Pedrotti, Luana Giongo; Curzel, Giovana Dallaio; Schuch, Jaqueline Bohrer; Bessel, Marina; Bordignon, Cláudia; Rosa, Mahira Lopes; Macedo, Gabriel de Souza; Rosa, Daniela Dornelles (Frontiers in Oncology, 2024)
Approximately 10% of breast cancer (BC) cases result from hereditary causes. Genetic testing has been widely implemented in BC care to determine hereditary cancer syndromes and personalized medicine. Thus, identification of individuals carrying germline PVs could be useful to provide appropriate prophylactic or screening measures for each BC subtype, however, there are few formal recommendations for genetic testing in this sense so far. In this study, we assessed rare germline variants in a specific group of genes in order to determine the association with human epidermal growth factor 2 enriched (HER2+) BC phenotype through a systematic review and meta-analysis comparing subtypes overexpressing HER2 with other clinically recognized subtypes of BC. This review was registered with PROSPERO (ID: CRD42023447571). We conducted an online literature search in PubMed (MEDLINE), Scopus, and EMBASE databases. We included original studies that investigated germline variants in HER2+ BC patients and selected the studies that reported only rare and/or pathogenic germline variants. We assessed the risk of bias and quality of the studies using the Joanna Briggs Institute Critical Appraisal checklists and the Modified Newcastle-Ottawa Scale for Genetic Studies, respectively. Considering hormone receptor and HER2 expression status, we compared gene-based risks initially in HR-HER2-, HR+HER2-, HR+HER2+, and HR-HER2+ groups, conducting separate meta-analyses using the random effects model for each comparison, and within them for each gene. Of the total 36 studies describing germline variants, 11 studies provided information on the prevalence of variants in the different clinically relevant BC subtypes and allowed comparisons. Germline variants within eight genes showed significant differences when metaanalyzed between the BC groups: BRCA1, BRCA2, TP53, ATM, CHEK2, PALB2, RAD51C, and BARD1. Notably, TP53, ATM and CHEK2 germline variants were identified as predisposing factors for HER2+ subtypes, whereas BRCA1, BRCA2, PALB2, RAD51C and BARD1 germline variants were associated with a predisposition to low HER2 expression. Main concerns about bias and quality assessment were the lack of confounding factors control; and comparability or outcome assessment, respectively. Nevertheless, our findings underscore the connection between germline variants and differential expression of the HER2 protein and BC subtypes.